Productivity gains from teleworking in the post COVID-19 era: How can public policies make it happen? (OECD Policy Responses to Coronavirus (COVID-19), 2020)
The ongoing health and economic crisis related to the COVID-19 pandemic and the required physical distancing measures force many firms to introduce telework (working from home) on a large scale. This may catalyse wider adoption of teleworking practices also after the crisis, with a wide range of impacts and uncertain net effects on productivity and other indicators. Public policies and co-operation among social partners are crucial to ensure that new, efficient and welfare-improving working methods emerging during the crisis are maintained and developed once physical distancing is over. To maximise the gains for productivity and welfare inherent in the use of more widespread telework, governments should promote investments in the physical and managerial capacity of firms and workers to telework and address potential concerns for worker well-being and longer-term innovation related in particular to the excessive downscaling of workspaces